If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2X + 2X = 68 Combine like terms: 2X + 2X = 4X 4X = 68 Solving 4X = 68 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Divide each side by '4'. X = 17 Simplifying X = 17
| myles=lie | | 4(x^2+6)=168 | | 10y^7+35y^6+25y^5= | | 9-5y=37+2y | | 2x^2=-4+6x | | 500=6x^3+5x^2 | | 2x^2=-4+6 | | 10x+8=4x+25 | | 12m+4n-6m+9n= | | Wow=suchCake | | 6x^2+54=108 | | 2(9X)+2(8X)=68 | | roman=lie | | 18(t-6)+3t=7(3t+2)-8 | | X+2x+4=34 | | 11c-4c= | | swag=pie | | 12-1/3u=12 | | y=8(8)+4 | | (w-5)/(w-1)=(w+2)/(w-3)+1 | | 2x-5=12-45 | | 16(3x-4)=4(12x+1) | | y=8(8)+7 | | 0.36=x/x | | 10pr+8p-5sr-4s= | | 1+2(3x-4)=3(5-x)-4 | | 2x^2-15x+7/6x^2-3x | | (275)(38/55)(11/25) | | x^2-2x=(7+x) | | (w-3)(w-7)=0 | | 4/17(x)=28 | | -3x+4=-2-2x |